The Nepticulidae and Opostegidae of mainland France and Corsica: an annotated catalogue (Lepidoptera: Nepticuloidea) - Nieukerken, Erik J. Van; Laštêvka, Aleš; Laštêvka, Zden-K (Zootaxa, 2006)
An annotated catalogue of the Nepticulidae and Opostegidae of mainland France (including Monaco) and Corsica is presented. All previous literature records are given and interpreted where necessary. We provide detailed records for material collected and studied by us. A total of 150 species of Nepticulidae and 6 species of Opostegidae are listed. All but one Nepticulidae are recorded from mainland France, 46 Nepticulidae and 2 Opostegidae are listed for Corsica, and two Nepticulidae and one Opostegidae for Monaco. The following species are recorded for the first time from France (mainland only): Stigmella carpinella (Heinemann, 1862), S. vimineticola (Frey, 1856), Trifurcula (Glaucolepis) magna A. & Z. LaštÁvka, 1997 and Ectoedemia hexapetalae (SzÝcs, 1957); Parafomoria halimivora Van Nieukerken, 1985 also is reported for France on re-interpretation of earlier literature records of P. helianthemella. New for mainland France but known from Corsica is Ectoedemia heringella (Mariani, 1939). New for Corsica, but previously known from France are: Stigmella luteella (Stainton, 187), Trifurcula (Levarchama) eurema (Tutt, 1899), T. (Trifurcula) josefklimeschi Van Nieukerken, 1990, T. (T.) calycotomella A. & Z. LaštÁvka, 1997, Bohemannia quadrimaculella (Boheman, 1853), and Ectoedemia (Ectoedemia) occultella (Linnaeus, 1767). The following species are removed from the list: Stigmella pretiosa (Heinemann, 1862) and S. poterii (Stainton, 1857), both from mainland France and Corsica, and Trifurcula (Trifurcula) pallidella (Duponchel, 1839) from mainland France, but it does occur in Corsica. The occurrence in France of Stigmella stelviana (Weber, 1938), Trifurcula (T.) serotinella (Herrich-Schäffer, 1855), and Ectoedemia arcuatella (Herrich-Schäffer, 1855) is confirmed, and for 15 species previously recorded in checklists, we provide the first detailed records for mainland France, and for four species for Corsica. The following new host records are given: Stigmella centifoliella (Zeller, 1848) reared from Alchemilla sp. (from label data of Chrétien); T. (Glaucolepis) magna reared from Thymus (from label data of Chrétien); T. (T.) silviae mines were found on Onobrychis viciifolia. The female genitalia of T. magna are illustrated and described for the first time. A lectotype is selected for Nepticula teucriella Chrétien, 1914 (now in Trifurcula (Glaucolepis)). The type locality for Trifurcula luteola is established to be in Alpes-de-Haute-Provence and not in Aude. The richest départements are: 66-Pyrenées-Orientales with 70 species, 77- Seine-et-Marne with 65 species, 68-Haut-Rhin with 58 and 33-Gironde with 57.